2021
DOI: 10.3390/ani11082277
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidative Impact of Dietary Vinegar and Rocket Salad on the Productivity, Serum Oxidation System, and Duodenal Histology of Chickens

Abstract: The purpose of the study was to investigate the ameliorative effect of dietary rocket salad and apple cider vinegar on the oxidative stress (OS) status of broilers. Specifically, 720 Ross 308 chicks were divided into six groups: negative and positive controls (NC and PC with and without additives, Vi1 and V12 experimental groups fed with diets mixed with 5 and 10 mL of vinegar/kg, and Ro1 and Ro2 groups fed with diets mixed with 2 and 3 g of rocket salad/kg, respectively). The experimental groups Vi1 and Vi2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Meanwhile, T5 was superior to T3 in improve FCR which explain the synergistic effect of Car instead of its individual using in diet for secretory stimulation of digestive enzymes involving trypsin, amylase, lipase and chymotrypsin in small intestine which markedly elevate the resbsorption of essential minerals for physiological process in quails body (Abdel-Fattah et al, 2014). High amount of water intake in T3, T4 and T5 could be speculated that any reason causes the toxic or stressful stimulation may lead to increase water consumption as attempt to palliate the OS and decrease levels of the prooxidant (LA) retained in tissues by accelerate its excretion through liver and 92 kidney (Mehrotra et al, 2008) and this result was recently confirmed by Al-Shammari and Batkowska (2021). Thus, there was increased relative weight of liver in those groups (Table 3).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Meanwhile, T5 was superior to T3 in improve FCR which explain the synergistic effect of Car instead of its individual using in diet for secretory stimulation of digestive enzymes involving trypsin, amylase, lipase and chymotrypsin in small intestine which markedly elevate the resbsorption of essential minerals for physiological process in quails body (Abdel-Fattah et al, 2014). High amount of water intake in T3, T4 and T5 could be speculated that any reason causes the toxic or stressful stimulation may lead to increase water consumption as attempt to palliate the OS and decrease levels of the prooxidant (LA) retained in tissues by accelerate its excretion through liver and 92 kidney (Mehrotra et al, 2008) and this result was recently confirmed by Al-Shammari and Batkowska (2021). Thus, there was increased relative weight of liver in those groups (Table 3).…”
Section: Discussionmentioning
confidence: 80%
“…From present results of stress indicators shown in Table 6 there were enhanced GPx, SOD, CAT, GSH, and FRAP levels and lowered LOOH, MDA, cortisol levels for quails in T5 and T4 followed by T3 in comparison to T2 which might interpret to a great extent the improved results in productive performance, ileal microbiome and nutrients digestibility. Similarly, growing body of evidence referred that was a reduction in blood antioxidant potential by reduction of antioxidative enzymes (SOD, CAT, GPx) and FRAP with increased levels of lipid peroxidations markers (MDA, LOOH) in stressed birds by lead acetate (Al-Shammari, 2017;Al-Shammari and Batkowska, 2021) or H 2 O 2 (Al-Shammari et al, 2019a;Al-Shammari et al, 2019b). Impaired redox status and negative stress markers in T2 could be linked to detrimental impact of lead to increase expression levels of caspase-3 and caspase-9 (apoptotic proteins) in vivo that responsible for apoptosis and breaking down functional proteins in hepatic tissue of quails (Arslan et al, 2022) and this could explain in turn the impairment in blood biochemical profile in T2 (Table 7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The leaves, oil, and seeds of the medicinal plant Eruca sativa have been used for a variety of therapeutic purposes since ancient times. It heals stomach and urinary diseases and enhances bile secretion, liver function, and digestion (8)(9)(10)(11). This plant is notable for its high content of crude protein and fat, as well as its abundance in vitamins E, C, and K, carotenoids, minerals, Iraqi Journal of Veterinary Sciences, Vol.…”
Section: Introductionmentioning
confidence: 99%